Editor’s Introduction: The Promise and Peril of Ranked Choice Voting - Tolbert, Caroline J. (2021)
Dissatisfaction with two-party politics is at an all-time high in the US. As extreme polarization and minority rule persist, a possibility of an electoral reform becomes increasingly more likely. This editor’s introduction discusses the ranked choice voting (RCV) as an alternative to the current single-member geographic districts with winner-take-all plurality elections in the US. The articles for this thematic issue critically evaluate whether RCV lives up to its promise in improving democracy in the US. Like any rule or institutional change, it has benefits and drawbacks. The empirical and historical research presented here focuses on the implementation and use of RCV in the US compared to other countries. This thematic issue offers new insights into the promise and perils of RCV as a way to aggregate votes in elections that ensure that the winning candidate receives a majority of the votes cast.